BASIS FOR JUDGES TO ADJUDICE IMMANTARIL COMPENSATION THAT CAN BE GIVEN TO VICTIMS IN RESTITUTION FOR CRIMINAL ACTS OF SEXUAL VIOLENCE BY CHILD PERPETRATORS - Yola Eska Afrina S; Nurini Aprilianda; Lucky Endrawati (CV. RADJA PUBLIKA, 2025)
Immaterial restitution for victims of Sexual Violence (TPKS) is an increasingly pressing issue in the criminal justice system. Although there are legal provisions governing victims' rights to receive compensation for non-material losses, court practice shows that the application of immaterial restitution in judges' decisions is still very limited. This causes immaterial restitution, an important aspect for victims accommodated in the justice system, but is often overlooked. This study aims to explore the basis used by judges in adjudicating immaterial restitution, as well as the guidelines that serve as a reference in the decision-making process. Understanding the basis for judges adjudicating immaterial restitution and the legal guidelines in making decisions is intended to ensure that judges' positions and powers to grant victims' rights can be freely used to adjudicate immaterial restitution in accordance with law and justice. Using a normative juridical approach, this study analyzes court decisions related to immaterial restitution, in order to identify the legal principles underlying judges' decisions. Through a review of various court decisions, this study found that there is a lack of clarity in the legal guidelines governing immaterial restitution, resulting in variations in their application by judges. Furthermore, this study also revealed that judges' understanding of the psychological and social impacts experienced by victims significantly influences their decisions. The lack of adequate training and resources for judges in this regard is a hindering factor. The results of this study are expected to contribute to the development of clearer and more comprehensive guidelines regarding immaterial restitution, as well as to encourage judges' increased understanding of the importance of this aspect in the judicial process. Thus, it is hoped that victims' rights can be recognized and protected more effectively, so that justice can be achieved not only through law enforcement against perpetrators, but also through appropriate reparations for victims.